Territorial resilience and cultural landscapes: the Cinque Terre National Park case study - Dorato,Elena (2020)
Abstract Current climatic, social and financial phenomena have triggered deep modifications in cultural landscapes, threatening their fragile territories and the communities that live in them. Nevertheless, they also represent a challenge to find a renewed link between forms of human activity and the production of landscape in order to understand its future evolutions. This paper deals with this field of investigation in the context of the Cinque Terre National Park, in Italy, through scenario planning criteria with the goal of rethinking the heritage-listed system of traditional terraced agriculture systems as an infrastructural element for a resilient territory. Starting from the Universal Soil Loss Equation (USLE), it identifies the main territorial factors of uncertainty and accordingly suggests possible intervention categories on the wider scale of the so-called slope units, through 2x2 matrixes. Defining a resilient transformation program for the environmental system of the Cinque Terre National Park over a twenty-year time frame means considering adaptability as a key aspect in different scenarios that might be generated in the near future.